The impact of selfies on body image satisfaction and the chain mediating role of self-objectification and narcissistic personality - Mei, Yaqi; Yang, Wenyu; Wang, Can (Frontiers in Psychology, 2024)
This study explores the mediating effect of self-objectification and narcissistic personality on the relationship between selfies and body image satisfaction. A total of 368 college students were administered a survey that included general information, selfie-related questions, a body image satisfaction scale, a body surveillance scale, and a narcissistic personality scale. Selfies, body image satisfaction, self- objectifica- tion, and narcissistic personality were shown to be positively correlated. Mediation modeling analysis found that selfies had a direct effect on body image satisfaction and that self-objectification and narcissistic personality mediated this relationship. Consequently, this study holds suggestions for researchers and educators searching for better exploration and attention to improve the content of education, guide students to set up a correct moral outlook, outlook on life and values.